RELASI DAN DAMPAK DESTINASI KAMPUNG WAYANG TERHADAP SOSIAL EKONOMI MASYARAKAT (Studi Pada Desa Kepuhsari Kecamatan Manyaran Kabupaten Wonogiri) - Triyanto Triyanto1; Kasidin Kasidin; Nina Adelina (Riset Manajemen dan Akuntansi, 2022)
There is a tendency that nowadays tourists prefer to travel to the village because the village gives other nuances that have not been found in modern tourism. Tourism to the village then gave birth to a concept called a tourist village, a rural tourism destination. Tourist visits will have an impact on socio-economic changes in rural communities. This research was conducted with the aim of knowing the relationship and impact of Kampung Wayang Destinations on the Socio-Economic Society of Kepuhsari village, Manyaran sub-district. This research is a descriptive survey method using an instrument in the form of a questionnaire. The population is 129 people, consisting of pokdarwis members, homestay owners and people who participate in the wayang village destination activities. By setting a sample of 30% taken proportionally to 39 respondents. The sampling technique used was simple random sampling. The analytical tool used is regression-correlation using SPSS software version 21. The results show that tcount = 5,492 > ttable = 2,026, then Ho is rejected and Ha is accepted so that there is a significant effect of Kampung Wayang Destinations on the Socio-Economic Society of Kepuhsari village, Manyaran sub-district. The relationship between the two is quite strong namely R=0,67. While the contribution of the wayang village destination to the socio-economic variation of the community R2 = 0,449  is 44.9%.